Harnessing Therapeutic Potentials of Statins Using Nanofibrous Carriers. (2nd November 2021) - Ataei, Mahshid; Roufogalis, Basil D.; Kesharwani, Prashant; Jamialahmadi, Tannaz; Sahebkar, Amirhossein
Abstract : Statins are a wide category of 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase inhibitor drugs extensively prescribed for hypercholesterolemia. In fact, many studies showed beneficial effects of these agents on a variety of related illnesses, which include increased atherosclerotic plaque stability, decreased proliferation of vascular smooth muscle, platelet aggregation, the dampening of vascular inflammation, and also anabolic effects on bone tissue. Therefore, these drugs are considered as pleiotropic agents having different clinical applications other than those for which they were initially developed. Controlled drug delivery is an efficient way of delivery in tissue engineering. Amongst different controlled release formulations, nanofibers are a novel, alternative, widely used agent because of their unique properties. These include their sustained release of drug, a high drug-loading capacity, flexible shapes with a high surface-to-volume ratio, and superior porosity. Electrospinning is an economic and a simple method employed to produce nanofibers. In this report, studies related to statin nanofiber applications have been reviewed and their results have been summarized. Four different applications of statin nanofibers have been reported, including bone generation, endothelial stenosis and thrombosis, peripheral nerve injury, and anti-inflammatory action. Studies carried out both in vitro and in vivo showed effectiveness of statins in bone healing, aneurysm, and the healing of sciatic nerve injury. In addition, statins showed apoptosis effects and anti-inflammatory effects, with dose-dependent reduction of IL-6 and dose-independent reduction of TNF- α . Despite these promising results, validation via clinical trials is yet to be performed. The scope of statins in their pleiotropic range of actions is still not completely explored, and studies are still needed to enlighten different useful aspects of such drugs.